Tertiary Education and Economic Growth in Tanzania - Kembo Bwana; Jeremiah Tumaini; Galan Mashenene (International Journal of Management, Accounting and Economics)
The study examines how tertiary education impact economic growth in Tanzania, time series secondary data spanning from the year 1999 to 2023 were extracted from World Bank database. Key explanatory variables were tertiary enrollment and government spending on tertiary education while dependent variable was economic performance measured by growth of gross domestic product. There were control variables such as inflation rate and population growth rate. After normalization of data, unit root test was performed and all variables were stationary after first difference. The study engaged bounds test for Autoregressive Distributed Lags (ARDL) Model and Error correction model as the results of existence of the co-integrating equations among the variables in the long run. Findings reveal that increase in expenditure on education and higher enrollment in tertiary education significantly enhance economic progress overtime. Conversely, short-term effects of educational investments are not immediately evident. Policy implications suggest that sustained investment in education, enhancing access and quality of tertiary education, and fostering public-private partnerships in education sector are crucial for long-term economic development. These insights underscore the pivotal role of education in driving economic prosperity.